2004
DOI: 10.1080/14034940310022223
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals' knowledge, attitudes, and experiences in relation to immigrant patients: a questionnaire study at a Danish hospital

Abstract: The study provides a foundation for new interventions and priorities within the healthcare system regarding immigrant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 15 publications
5
57
0
9
Order By: Relevance
“…As in previous studies, several participants have identified stereotyped and discriminatory attitudes of health professionals, which include lack of sympathy, use of discriminatory language or even hostile attitudes toward immigrants (Campayo et al 2006;Michaelsen et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies, several participants have identified stereotyped and discriminatory attitudes of health professionals, which include lack of sympathy, use of discriminatory language or even hostile attitudes toward immigrants (Campayo et al 2006;Michaelsen et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that more frequent contact with immigrant patients may lead to more positive attitudes (Michaelsen, Krasnik, Nielsen, Norredam, & Torres, 2004) while others warn that increased contact in the absence of formal training activities may, in fact, lead to an erosion of positive attitudes (Wear & Kuczewski, 2008). Other factors, such as the physician's sociodemographic characteristics and personal history, prior exposure to other cultures, and patient care experiences may also play a role.…”
Section: Introductionmentioning
confidence: 92%
“…Health care professionals often perceive migrant patients to be culturally and socially different from ethnic majority patients, which may cause ethnic disparities in service delivery (Michaelsen, Krasnik, Nielsen, Norredam, & Torres, 2004;Richardson, Thomas, & Richardson, 2006;van Ryn, Burgess, Malat, & Griffin, 2006;van Ryn & Fu, 2003). Although European studies on migrant cancer patients are few and have tended to focus on disease concepts and access to services exclusively among migrant groups (Randhawa & Owens, 2004), some studies have included the ethnic majority (Grange et al, 2008;Papadopoulos & Lees, 2004).…”
Section: Introductionmentioning
confidence: 95%